Liquid-liquid equilibria of ternary mixtures containing Aniline plus Toluene plus water at elevated temperatures: measurements and correlation - Gaikwad, Shashank G.; Pathak, Abhishek A.; Mote, Dhananjay R.; Gogate, Parag R.; Singh, Shivani; Modhera, Bharat (Separation Science and Technology, 2023)
Liquid-liquid equilibrium (LLE) data for the ternary system, Aniline + Toluene + Water, was measured at different temperatures of 298.15 K, 313.15 K and 323.15 K under atmospheric pressure with the help of High-Performance Liquid Chromatography (HPLC) analysis and Karl-Fischer technique. The efficiency of Toluene to extract Aniline from aqueous phase was then quantified in terms of the distribution coefficient and separation factor based on the tie line data. The system showed very good separation ability quantified in terms of high values of distribution factor (average around 7) and separation factors (as high as 1000). The experimental tie line data was verified by Hand and Othmer-Tobias equations. The LLE data was also correlated using NRTL and UNIQUAC models and both of them were able to represent the behavior of the system accurately when tested against experimental results. Toluene has been demonstrated to be very efficient to extract Aniline from reaction mixture, which is typically a by-product in hydrogenation of nitrobenzene, a process commercially used to produce p-Aminophenol in industry.
Keywords: Aniline; LLE; NRTL; Tie line; Toluene; UNIQUAC